Gain enhancement of terahertz patch antennas by coating epsilon-near-zero metamaterials. (March 2020) - Cheng, Cong; Lu, Yuanfu; Zhang, Dongbo; Ruan, Fangming; Li, Guangyuan
Abstract: In this work, we propose a novel approach to enhance the gain of a terahertz patch antenna by coating an epsilon-near-zero (ENZ) metamaterial superstrate. The ENZ metamaterial is composed of indium antimonide (InSb) and silicon dioxide multilayers, of which the out-of-plane component of the effective permittivity is close to zero. Results show that by coating the ENZ superstrate the peak gain of the antenna is increased from 5.37 dB to 7.79 dB, corresponding to 45% gain enhancement and greatly improved radiation directivity. We find that the ENZ frequency of the multilayer metamaterial equals to that of semiconductor InSb and thus it can be tuned dynamically. We expect the concept of adding a multilayer ENZ metamaterial superstrate to enhance the antenna gain will find potential applications in other types of terahertz antennas and in antennas in other frequency regimes. Highlights: A novel ENZ metamaterial superstrate was proposed to enhance the gain of a terahertz patch antenna. The ENZ metamaterial superstrate is composed of alternating InSb and SiO2 multilayers. The gain of a terahertz patch antenna is improved by 45% from 5.37 dB to 7.79 dB. The metamaterial ENZ frequency is found to be determined by that of semiconductor InSb, thus enabling dynamical tuning. The theory and operation principle are explained. Effects of key parameters are discussed.